Performance Analysis of Flat Gain Wideband Raman Amplifier for S+C and C+L Band DWDM System. (15th August 2018) - Pradhan, Dipika D.; Mandloi, Abhilash
Abstract : Raman amplifier is an open area of research in telecommunication field. This paper discusses the performance of 64 channels of 10 Gbps WDM systems with backward multipump Raman amplifier. The main goal of this paper is the optimization of Raman amplifier to minimize its gain variation without using any gain flattening techniques. To increase the transmission capacity of DWDM system, Raman amplifier with backward multipump configuration is implemented. The optimized parameters such as pump power and frequencies are used to deliver both ground and excited state absorption for amplification in S+C and C+L band region. The pump power and frequencies are optimized through multitarget and multiparameter optimization tool available in OptiSystem software. Gain ripple was achieved <0.5 dB for this simulation setup. The maximum flat gain achieved is 8.6 dB and noise figure of <8 dB was achieved for this wide bandwidth without using gain flattening techniques. This amplifier design will be helpful for CATV applications and telecommunication networks.